In vitro antimicrobial effect of different root canal sealers against oral pathogens - Ali Monajemzadeh; Sina Ahmadi; Sajad Aslani; Batool Sadeghi-Nejad (Mazandaran University of Medical Sciences, 2017)
Background and Purpose: Root canal therapy is the primary method for the treatment of an infected pulp in modern dentistry. The main aim of endodontic treatment is the elimination of bacteria and their products from infected root canals. In this study, we attempted to investigate the antimicrobial activity of three root canal sealers against oral pathogens. Materials and Methods: The antimicrobial effectiveness of three endodontic sealers with different chemical compositions, namely resin (AH 26), zinc oxide eugenol (ZOE), and mineral trioxide aggregate (MTA), against Candida albicans, Streptococcus sanguis, Streptococcus salivarius, Streptococcus mutans, and Lactobacillus casei was assayed by agar well diffusion method (AWDM). The tested sealers were prepared according to the manufacturer’s instructions and poured in the prepared wells of agar plates; diluted inocula (105 and 106 CFU/ml) of the tested microorganism strains were also used. The minimum inhibitory concentration (MIC) values of the selected canal sealers ranged between 3.12 and 50 mg.ml-1 against the employed microorganism strains. All the plates were incubated at 37°C under anaerobic condition for bacteria and at 30°C for C. albicans. After three days, the inhibition zones were measured.  Results: In this investigation, AH 26 exhibited strong activity against C. albicans with the minimum inhibitory concentration of 12.5 mg.ml-1, but ZOE and MTA did not act against C. albicans. ZOE sealer had the highest antimicrobial activity against the tested bacteria, while MTA showed the lowest antimicrobial activity.  Conclusion: The ascending sequence of microbial growth inhibition zones was as follows AH 26 > ZOE > MTA.